The role of electronic health tools in unwanted pregnancy prevention, abortion and post-abortion follow-up: A systematic review - Seyedeh Nafiseh Shahrokhi; Hosna Salmani; Maryam Ahmadi (Wolters Kluwer Medknow Publications, 2023)
Background: More than 30% of women experience at least one abortion. To date, there has been no comprehensive mobile health project on the impact of technology on access to abortion, contraception, and post-abortion follow-up. The purpose of this study was to review published studies on the role of electronic health in the prevention of unwanted pregnancy, abortion, and post-abortion follow-up. Materials and Methods: The Web of Science, PubMed, ScienceDirect, and EMBASE databases were searched to find relevant articles published between 2008 and 2018. A systematic review study was conducted on 33 relevant articles. All studies related to the use and impact of electronic health on unwanted pregnancy prevention, abortion and post-abortion follow-up in English from January 2008 to December 2018 were included. The quality of the studies was evaluated using the PRISMA-S. Results: Thirty-three studies met the inclusion criteria for the review. The Studies were divided into four main groups of women's experiences on the use of mobile health and telemedicine technologies for at-home medical abortion, unwanted pregnancy prevention, abortion, and post-abortion follow-up. The results showed the significant impact of using electronic health on unwanted pregnancy prevention, abortion, and post-abortion follow-up. Conclusions: Health technologies have the potential to be used as a low-cost and accessible method to replace abortion services. They can facilitate remote care and quick access to information to complete the gaps in access to abortion. Therefore, it is necessary for health service providers to be aware of the possibility of the client's access to electronic health tools.